Корректировка режимов упрочнения пластическим деформированием - Наумова, Е. А.; Мосьпан, Д. В.; Воронин, А. В.; Драгобецкий, В. В. (НТУ "ХПИ", 2014)
Рассмотрены особенности эксплуатации машин и агрегатов в условиях современного производства. Новым направлением при разработке изделий с высокими эксплуатационными характеристиками является получение наноструктурных композиционных материалов и материалов с преобразованной упорядоченной структурой. Деформационная неустойчивость возникает при деформациях равных предельным равномерным. Предложены методы теоретического определения предельных равномерных деформаций, что позволяет оптимизировать процессы упрочнения пластическим деформирования, калибровки и формоизменения деталей с элементами жесткости.

The characteristics of operation of machines and plants in the conditions of modern production are investigated. A new direction in the development of products with high performance is to obtain nanostructured composite materials and materials with a transformed ordered structure. Experimantal and theoretical analysis of hardening processes are performed. Several directions of hardening methodologies are investigated. The second direction is more economical and less energy consumptive. Formation of ordered structures is most likely in conditions of heat, deformation and power imbalance. Deformation instability occurs when strain is uniform limit. Methods of determining the theoretical limit of uniform strain are offered. The use of the results allows to optimize the processes of plastic deformation hardening, calibration and forming parts with stiffener P.
Mode correction of plastic deformation hardening
Keywords: пластические деформации; упрочнение; методы определения; машины; деформационная неустойчивость; агрегаты; plastic deformation; stability; structure; hardening